ANALISIS KEDISIPLINAN PEGAWAI TERHADAP TUGAS POKOK DAN FUNGSI PEGAWAI PADA KANTOR LURAH RAMPOANG - Amra; Musafir Jasin; Gebi Indra Prayoga (CV. Aksara Global Akademia, 2023)
Main tasks and functions in general are things that an employee in an agency must or even must carry out on a regular basis in accordance with his or her abilities to complete the work program that has been created based on objectives. This research aims to (1) find out the discipline of employees at the village head's office. Rampoang, Bara sub-district, Palopo city (2) knows how well the employees are disciplined towards the main duties and functions of employees at the Rampoang village head office. The research method used in this research is a qualitative method, with data collection techniques through observation, interviews, library studies and documentation. Results This research shows that (1) Employee discipline has not been fully implemented well in the Rampoang village head office, Bara subdistrict, Palopo city, seen from 4 indicators of work discipline which include punctuality, using office equipment properly, high responsibility and compliance with office rules. These four indicators are punctuality and compliance with office rules which have not gone well because there are still employees who often commit violations, especially in terms of working time discipline. However, the use of office equipment and the high level of responsibility held by employees at the Rampoang subdistrict office have been carried out well. (2 ) the main duties and functions of employees at the Rampoang Village Head's office, Bara District, Palopo City, which were assessed based on service and empowerment aspects, have been carried out well